The Pivotal Role of Transient Receptor Potential Channels in Oral Physiology - Chalazias, Andreas; Plemmenos, Grigorios; Evangeliou, Evangelos; Piperi, Christina (Current Medicinal Chemistry, 2022)
Background: Transient Receptor Potential (TRP) Channels constitute a large family of non-selective permeable ion channels involved in the perception of environmental stimuli with a central and continuously expanding role in oral tissue homeostasis. Recent studies indicate the regulatory role of TRPs in pulp physiology, oral mucosa sensation, dental pain nociception and salivary gland secretion. This review provides an update on the diverse functions of TRP channels in the physiology of the oral cavity, with emphasis on their cellular location, the underlying molecular mechanisms and clinical significance. Methods: A structured search of bibliographic databases (PubMed and MEDLINE) was performed for peer-reviewed studies on the function of TRP channels on oral cavity physiology in the last ten years. A qualitative content analysis was performed of screened papers and a critical discussion on the main findings is provided. Results: TRPs expression has been detected in major cell types of the oral cavity, including odontoblasts, periodontal ligament, oral epithelial, salivary gland cells, and chondrocytes of temporomandibular joints, where they mediate signal perception and transduction of mechanical, thermal, and osmotic stimuli. They contribute to pulp physiology through dentin formation, mineralization, and periodontal ligament formation, along with alveolar bone remodeling in the dental pulp and periodontal ligament cells. TRPs are also involved in oral mucosa sensation, dental pain nociception, saliva secretion, swallowing reflex and temporomandibular joints' development. Conclusion: Various TRP channels regulate oral cavity homeostasis, playing an important role in the transduction of external stimuli to intracellular signals in a cell typespecific manner and presenting promising drug targets for the development of pharmacological strategies to manage oral diseases.
Keywords: salivary glands